Prediagnostic circulating inflammation biomarkers and esophageal squamous cell carcinoma: A case–cohort study in Japan. Issue 3 (3rd December 2019) - Aversa, John; Song, Minkyo; Shimazu, Taichi; Inoue, Manami; Charvat, Hadrien; Yamaji, Taiki; Sawada, Norie; Pfeiffer, Ruth M.; Karimi, Parisa; Dawsey, Sanford M.; Rabkin, Charles S.; Tsugane, Shoichiro; et al.
Abstract : Esophageal squamous cell carcinoma (ESCC) is the predominant histologic subtype of esophageal cancer worldwide. Measurements of circulating inflammation‐related biomarkers may inform etiology or provide noninvasive signatures for early diagnosis. We therefore examined levels of inflammation molecules for associations with ESCC risk. Using a case–cohort study designed within the Japan Public Health Center‐based Prospective Study, we measured baseline plasma levels of 92 biomarkers using a multiplex assay in a subcohort of 410 randomly selected participants and 66 participants with incident ESCC (including four cases that occurred in the subcohort). ESCC hazard ratios (HRs) were calculated for 2–4 quantiles of each biomarker by Cox proportional hazards regression models with age as the time metric, adjusted for sex, smoking and alcohol use. Twenty analytes were undetectable in nearly all samples. Of the remaining 72, 12 biomarkers (FGF19, ST1A1, STAMBP, AXIN1, CASP8, NT3, CD6, CDCP1, CD5, SLAMF1, OPG and CSF1) were associated with increased ESCC risk ( p trend  < 0.05) with HRs per quantile 1.28–1.65. Seven biomarkers (CXCL6, CCL23, CXCL5, TGFA, CXCL1, OSM and CCL4) were inversely associated with HRs 0.57–0.72. FGF19, CASP8, STAMBP, ST1A1 and CCL‐4 met statistical significance with false discovery rate correction. Associations did not differ <5 vs . ≥5 years between blood collection and ESCC diagnosis. CASP8, STAMBP and ST1A1 were strongly correlated ( p  < 0.05). Our study expands the range of inflammation molecules associated with the development of this highly lethal neoplasia. Correlations among these novel biomarkers suggest a possible shared pathway. These findings need replication and could further delineate ESCCs molecular mechanisms of carcinogenesis. What's new?: Chronic inflammation has long been considered an important contributor to carcinogenesis. Circulating levels of inflammation‐related biomarkers may thus provide valuable information regarding cancer etiology, and may eventually aid in the early diagnosis of some cancers. In this study, the authors identified five such proteins that are associated with esophageal squamous cell carcinoma (ESCC) risk. These biomarkers may improve our understanding of ESCC etiology, enhance non‐invasive, molecular diagnostic panels, and may provide potential therapeutic targets.